A Tool to Implement Adaptive Audio Techniques on Unity Games - Rodrigues, Miguel F.; Coutinho, Flávio R. S. (Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames), 2021)
Developing an effective and simple audio system that can adapt to in-game events can take time and become complex, specially to beginner developers that don’t know how to use adaptive audio techniques. To make this less challenging, we developed a tool to implement adaptive audio into Unity games. The Adaptive Audio Manager tool for Unity is an accessible package that provides classes and methods which help developers implement a functional audio system in their games, using two popular adaptive audio techniques: vertical layering and horizontal re-sequencing. Along with the framework code, we provide documentation and a Unity prototype project with examples to keep the learning process on how to use this framework simple.